The Correlation Between Nutritional Status with Hypertension Cases of Elderly Women in Central Java Province - Wiwik Wuandari; Farida Nur Isnaeni; Dyah Intan Puspitasari; Nur Lathifah Mardiyati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Hypertension is still the highest problem in non-communicable diseases (NCD) in Indonesia and has increased cases from previous years. One of the factors that cause hypertension is nutritional status. Objective: This study aimed to find the correlation between nutritional status and hypertension cases of elderly women in Central Java Province. Methodology: This is an observational study with cross-sectional design using secondary data. Nutritional and hypertension status in Central Java Province was derived from Baseline Health Research 2018. A total of 994 Central Java residents aged 55-64 years were used. Hypertension status was obtained from the average of three measurements of systolic/diastolic blood pressure and nutritional status according to BMI obtained from the body weight and height measurement. The chi square test with a 95% confidence level were used to analyzed the data. Results: Most of the respondents was elderly (55-59 years old) (56%), working (65.6%), had normal nutritional status (43.1%) and had hypertension (66.2%). There was a significant correlation between nutritional and hypertension status of elderly women in Central Java Province (p = 0.000). Conclusion: Nutritional status is one of the factors contributing in the insidence of hypertension. Therefore, health program in improving nutritional status is needed in order to reduce the prevalence of hypertension.